2016
DOI: 10.3233/jad-151037
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Brain Iron Accumulation in Vascular Dementia and Alzheimer’s Dementia Using Quantitative Susceptibility Mapping Imaging

Abstract: Increased iron deposition in the putamen and caudate nucleus in VaD and AD patients was not associated with age or the severity of cognitive deficits. Further evaluations are needed to determine the temporal changes in iron load and their diagnostic role in dementia pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
84
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(91 citation statements)
references
References 43 publications
6
84
0
1
Order By: Relevance
“…Then, we selected iron-rich subcortical nuclei as regions of interest (ROI) to assess the association between the susceptibility values of these ROIs with cognitive performance. ROIs were selected in accordance with previous studies and included the pulvinar nucleus of the thalamus, head of caudate nucleus, globus pallidus, putamen, hippocampus, substantia nigra, and red nucleus (Liu et al, 2015a; Moon et al, 2016). Figure 2 presents examples of the seven ROIs.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, we selected iron-rich subcortical nuclei as regions of interest (ROI) to assess the association between the susceptibility values of these ROIs with cognitive performance. ROIs were selected in accordance with previous studies and included the pulvinar nucleus of the thalamus, head of caudate nucleus, globus pallidus, putamen, hippocampus, substantia nigra, and red nucleus (Liu et al, 2015a; Moon et al, 2016). Figure 2 presents examples of the seven ROIs.…”
Section: Methodsmentioning
confidence: 99%
“…The significance levels were set at p < 0.05 for all analyses. To assess the reliability of measurement in segmenting ROI, we selected the MR images of 10 normal subjects in accordance with a previous study (Moon et al, 2016). Another rater independently measured the ROIs for each anatomical target.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study reported the increase of susceptibility (iron load) in vascular dementia as well as AD (Fig. 12) (141). …”
Section: Structural Imagingmentioning
confidence: 99%
“…The potential clinical usefulness of QSM also has been shown in multiple sclerosis [6, 43], lupus erythematosus [44], Alzheimer's disease [45], Parkinson's disease [46], multifocal leukoencephalopathy [47], cerebral perfusion [41], hemorrhage [9, 48], function MRI [12, 42] in brain, and some applications in aorta, breast, extremity, kidney, and so forth [14, 42, 49]. Improving accuracy of QSM will profit these approaches.…”
Section: Discussionmentioning
confidence: 99%